Membangun Kesiapsiagaan Anak dalam Menghadapi Gempa Bumi: Pemberdayaan Masyarakat di TPA Misbahul Jannah Boyolali - Fajar Ruddin; Nurjihaana El Fathiin; Melani Rahmawati (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
Children are a vulnerable group in disaster situations due to their limited understanding of risks and underdeveloped self-protection abilities. This community service activity aimed to improve children's earthquake preparedness through interactive psychological education and simulation approaches. The target participants of this community service program were 32 students of the Taman Pendidikan Al -Qur'an (TPA) Misbahul Jannah, Boyolali. The methods employed included: (1) interactive disaster education sessions using visual media; (2) safety action training through the drop, cover, and hold on technique; and (3) earthquake emergency response simulation. Evaluation was conducted through question-and-answer sessions and direct observation of participants' ability to practice safety steps. The results showed an increase in participants' understanding of earthquake risks and the safety actions to be taken. Most participants were able to articulate safety steps and perform the simulation correctly. This activity is expected to serve as a model for disaster preparedness education based on non-formal religious educational institutions, replicable in other TPAs in disaster-prone areas.